2020
DOI: 10.1111/jcmm.15142
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA YAP1 acts as the sponge of microRNA‐21‐5p to secure HK‐2 cells from ischaemia/reperfusion‐induced injury

Abstract: Acute kidney injury (AKI), a kind of syndrome with sudden degradation of renal function, is characterized by loss of urine creatinine. 1 With 7.0% incidence in China, AKI becomes a representative public health matter that ranges from newborns to senior citizens. 2 AKI is divided into pre-kidney, intrinsic and post-kidney, of whose pathophysiology risk factors include inflammatory diseases, 3 traumatism 4 and drug overdose. 5 In addition, ischaemia/reperfusion (I/R) during kidney transplantation also is extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…CircRNA_15698 promotes the accumulation of extracellular matrix‐related proteins by blocking miR‐185 9 . Circular RNA YAP1 was reported to protect the kidney HK‐2 cells from ischaemia/reperfusion injury by acting as a sponge of miR‐21‐5p 19 . It was shown that miR‐218 plays a key regulator in the progression of multiple human cancers, but its effects on DN remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA_15698 promotes the accumulation of extracellular matrix‐related proteins by blocking miR‐185 9 . Circular RNA YAP1 was reported to protect the kidney HK‐2 cells from ischaemia/reperfusion injury by acting as a sponge of miR‐21‐5p 19 . It was shown that miR‐218 plays a key regulator in the progression of multiple human cancers, but its effects on DN remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al [ 140 ] reported that the circRNA yes-associated protein 1 (circYAP1) expression was downregulated in AKI patients as well as in I/R-treated HK-2 cells. circYAP1 overexpression promoted cell growth and attenuated the secretion of inflammatory factors and ROS generation in HK-2 cells under I/R treatment.…”
Section: Lncrna/circrna-mirna-mrna Axis In Irimentioning
confidence: 99%
“…CircRNAs are competitive endogenous RNAs (ceRNAs) that regulate gene expression by sponging their target miRNAs [ 30 32 ]. For example, circular RNA YAP1 protects against ischemic injury by regulating the miRNA-21-5p/PI3K/AKT/mTOR axis [ 33 ]. CircLRP6 was found to act as a sponge for miR-205 to regulate proliferation, oxidative stress, ECM accumulation, and inflammation in mesangial cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%